2019
DOI: 10.1063/1.5094894
|View full text |Cite
|
Sign up to set email alerts
|

Determination of NO densities in a surface dielectric barrier discharge using optical emission spectroscopy

Abstract: A new computationally assisted diagnostic to measure NO densities in atmospheric-pressure microplasmas by Optical Emission Spectroscopy (OES) is developed and validated against absorption spectroscopy in a volume Dielectric Barrier Discharge (DBD). The OES method is then applied to a twin surface DBD operated in N2 to measure the NO density as a function of the O2 admixture (0.1%–1%). The underlying rate equation model reveals that NO(A2Σ+) is primarily excited by reactions of the ground state NO(X2Π) with met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The geometry used in this simulation is selected as the same in Reference [31], intended for applications in pollutant remediation and gas treatment. This kind of configuration of an S‐DBD has been investigated experimentally for gas flow purification, [ 37 ] value‐added gas measurement, [ 38 ] conversion of volatile organic compounds, [ 39 ] different oxygen admixture, [ 40 ] which described a twin electrode S‐DBD in detail.…”
Section: Simulation Conditions and Numerical Modelmentioning
confidence: 99%
“…The geometry used in this simulation is selected as the same in Reference [31], intended for applications in pollutant remediation and gas treatment. This kind of configuration of an S‐DBD has been investigated experimentally for gas flow purification, [ 37 ] value‐added gas measurement, [ 38 ] conversion of volatile organic compounds, [ 39 ] different oxygen admixture, [ 40 ] which described a twin electrode S‐DBD in detail.…”
Section: Simulation Conditions and Numerical Modelmentioning
confidence: 99%
“…The geometry to be simulated is chosen to resemble that of the twin SDBD electrode intended for use in gas treatment applications and was first experimentally presented in [24] and subsequently in [25][26][27]45]. The authors defer the readers to these references for a detailed description of the twin SDBD system under question.…”
Section: Computational Modelmentioning
confidence: 99%
“…The geometry to be simulated is a cross section of the twin SDBD described in [24][25][26][27]45], and shown in fig. 3.…”
Section: Simulated Geometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Their further research demonstrated that secondary ionization waves occurred at the edge of the HVE during streamer extension [13]. In addition, the surface charge sensors [14,15], dielectric temperature [16] and optical emission spectroscopy [17] are also utilized to provide insight into the discharge characteristics and discharge process of SDBD.…”
Section: Introductionmentioning
confidence: 99%